(untitled) (Critical Journal of Social Sciences, 2026)
Among the four pillars of Gross National Happiness (GNH), the one that has probably been the most under-researched is the fourth pillar – preservation and promotion of culture. This is the critical pillar that has particular relevance – not just for Bhutan – but for the local and cultural context of countries in the Global South. This paper attempts to address this gap in knowledge and evidence. The paper will argue that the local wisdom based on indigenous knowledge systems (IKS) of the Karen hilltribe people in Northern Thailand and as experienced in their everyday life experiences over generations, has generated a large body of knowledge, knowhow and evidence that is yet to be fully tapped for peoples’ development. It is therefore critical to identify and establish the relationship of culture and local wisdom to development and social wellbeing (happiness) which can contribute to improved livelihoods and sustainable development. Sustainable development, therefore, is only possible when it is based on the foundational principles and values of local wisdom (knowledge and practices) as it exists and is reproduced in the lives of people across generations. The paper will present the local wisdom of the Karen hilltribe communities that has traditionally been the foundation of their cultural and social wellbeing until today. Taking the example of the “rice-merit making ceremony” as practiced among these communities for generations, the paper will show how the principles and values on which this tradition – called the “religio-cultural approach” - has become the foundation of individual and social wellbeing – contributing to self-identity, community solidarity, sharing and improved livelihoods. This approach based on local wisdom is both a worldview and a pathway for achieving – what I call “Gross Peoples’ Happiness” (GPH).